Effects of Chronic Disease Control Club on Physical Activity, Anxiety, and Blood Sugar Level: A Path Analysis Evidence - Fajar Alam Putra; Dono Indarto; Ruben Dharmawan (Journal of Health Promotion and Behavior, 2019)
Background: Diabetes mellitus (DM) is a serious chronic disease with a tendency to worsen. The number of DM cases worldwide in 2015 was 415 million people and is expected to increase by 642 million cases in 2040. Indonesia ranks 7th in the world with 10 million DM cases in 2015, around 90% of which are Diabetes Mellitus Type 2. This study aimed to determine the effects of chronic disease control club on physical activity, anxiety, and blood sugar level.Subjects and Method: This was a cross sectional study conducted at Sukoharjo health center, Sukoharjo, Central Java, from August to September 2018. A sample of 245 type 2 DM patients was selected for this study. The independent variables were physical activity, anxiety, chronic disease control club, and complications. Data were collected using HARS, physical activity, complication and club activitiesquestionnaires. Data were analyzed by using path analysis.Results: Anxiety directly increased with complication (b= 12.55; 95% CI= 111.98 to 13.90; p<0.001). Anxiety directly decreased with chronic disease control club (b= -3.29; 95% CI= -4.72 to -1.85; p<0.001). Fasting blood sugar directly increased with anxiety (b= 2.78; 95% CI= 1.32 to 4.24; p<0.001) and complication (b= 33.14; 95% CI= 8.40 to 57.87; p= 0.009). Fasting blood sugar directly decreased with physical activity (b= -15.12; 95% CI= -19.89 to -10.35; p<0.001) and chronic disease control club (b= -30.14; 95% CI= -48.80 to -11.48; p= 0.002).Conclusion: Anxiety directly increases with complication. Anxiety directly decreases with chronic disease control club. Fasting blood sugar directly increases with anxiety and complication. Fasting blood sugar directly decreases with physical activity and chronic disease control club.Keywords: blood sugar level, physical activity, anxiety, chronic disease control clubCorrespondence: Fajar Alam Putra. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: bolodewe88@gmail.comJournal of Health Promotion and Behavior (2019), 4(3): 137-144https://doi.org/10.26911/thejhpb.2019.04.02.06